PELATIHAN MEMBUAT PRODUK DIGITAL EDUKASI BERBASIS AI - Syamsurijal; Gawise Gawise; Suarti Suarti; Masri Masri (BESIRU : Jurnal Pengabdian Masyarakat, 2026)
The development of Artificial Intelligence (AI) technology has created new opportunities for developing educational digital products that are beneficial not only for learning activities but also for generating economic value. However, the use of AI in society remains largely limited to information retrieval and administrative purposes, highlighting the need for community empowerment programs that focus on productive digital skills. This community service program aimed to enhance participants’ abilities to utilize AI in creating high-quality and marketable educational digital products. The activity was conducted online via Zoom using lectures, demonstrations, hands-on training, mentoring, and discussion sessions based on a learning-by-doing approach. The training stages included creating illustrations using ChatGPT, compiling products into PDF format through iLovePDF, converting them into interactive flipbooks using Heyzine, creating Lynk.id accounts, setting product prices, and promoting products through TikTok. The results showed that participants successfully developed various educational digital products, including illustrated storybooks, learning modules, and digital literacy media that were ready for online marketing. In addition to improving technical competencies in AI utilization, participants also gained knowledge of digital marketing strategies and product monetization. The program contributed to strengthening digital literacy, creativity, and entrepreneurial skills, thereby creating opportunities for additional income generation within the digital economy.